Business Networking, Innovation, and Firm Competitiveness: The Case of Handicraft Industry in Indonesia - Hendayana, Yayan; El-Kafafi, Siham; Waskito, Meindro; Faeni, Dewi Puspaningtyas (Universitas Bangka Belitung, 2024)
This study aims to examine the influence of business networking and innovation on firm competitiveness in the case of the handicraft industry in Indonesia. The sample in this study was the owner of the Handicraft Industry in Indonesia. The hypotheses were analyzed by using the structural/equation modeling (SEM) approach. The result showed that business networking and innovation positively influence the competitiveness of the handicraft industry in Indonesia. This paper gives additional insights into the relationship between business networking, and innovation on firm competitiveness in handicraft industry context in Indonesia, and the innovation can mediate the influence of business networking on firm competitiveness. Business networking capabilities must receive important attention from SMEs, especially in the creative industry in the craft sector. SMEs must establish good communication with customers, suppliers, and competitors. There is only one independent variable in this research, namely business network, so it is less comprehensive. To be more comprehensive, other independent variables can be added such as technological ability, marketing knowledge, and entrepreneurial ability.